(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The Past tenses in the Kazakh language differ from other tenses first of all by the variety and complexity of their semantic connotations. The Past form with the participle suffix –yp is different from other forms of tenses not only by itssemantic, but also by morphological indicators. The functional and semantic characteristics of this tense are revealed in the course of studying its usage in different situations. The article focuses on the functional and semantic characteristics of the Past Form, which is formed with the Participle suffix -yp. The purpose of the study is to reveal all the possible functional and semantic characteristics of the Past Form with the Participle suffix -yp within the light of the selected examples.